Pengaruh Keterampilan Interpersonal, Kecerdasan Emosional dan Motivasi Ekstrinsik Terhadap Kinerja Karyawan Bank Central Asia Cabang Medan - Susanti, Sintia (Journal of Management and Economics Research, 2023)
Whether or not performance is successful is influenced by several factors, namely motivation, discipline, and interpersonal skills both individually and in groups. Based on this description, the authors are interested in conducting research with the title: "The Effect of Interpersonal Skills, Emotional Intelligence and Extrinsic Motivation on Employee Performance of PT Bank Central Asia Tbk. Medan Branch". This study aimed to determine and analyze the effect of interpersonal skills, emotional intelligence, and extrinsic motivation on the performance of PT Bank Central Asia Tbk employees. Medan Branch both partially and simultaneously. The population in this study was 67 people and the sample was 67 respondents using the saturated sample method. The test used is multiple linear regression and hypothesis testing. The results of this study indicate that interpersonal skills have a significant effect on employee performance, emotional intelligence has a significant effect on employee performance and extrinsic motivation has a significant effect on employee performance. Simultaneously, the variables of interpersonal skills, emotional intelligence, and extrinsic motivation significantly affect employee performance at PT Bank Central Asia Tbk. Medan Branch.